SICHJO A GENRE THAT CALLS FROM LUXURY TO NATURE (American Journal of Pedagogical and Educational Research, 2023)
This article deals with the genre of “Sichjo” that originated in Korea during the Joseon (Li) Literature period (1392-1910). This genre is considered a lyrical genre with a certain image of excitement and experience, which embodies the traditions of Korean folklore and the three religious-philosophical teachings of the peoples of the Far East (Confucianism, Buddhism and Taoism).